Organizational commitment in local government bureaucracies: The case of Zambia - Resnick, Danielle; Siame, Gilbert (Wiley, 2023)
What drives organizational commitment in local government? Despite the growth of decentralization initiatives in many developing countries and concurrent investments by international donors to build public sector capacity, there thus far has been little consideration of what drives bureaucrats to stay committed to local government service. This paper addresses this question by drawing on original survey data with more than 150 bureaucrats across 16 district councils in Zambia. The findings show that along with education, key factors that shape commitment include alignment with the mission of local government service, clear job objectives provided by supervisors, and placement in a city council. By contrast, extrinsic rewards and political interference play a more important role when examining drivers of job satisfaction. The results underscore the need for nuanced and multi‐modal policy interventions in developing country contexts to retain skilled staff in local government and improve the delivery of services to local communities.